2014
DOI: 10.1002/ppsc.201300232
|View full text |Cite
|
Sign up to set email alerts
|

Science and Engineering of Graphene Oxide

Abstract: 619wileyonlinelibrary.com www.particle-journal.com www.MaterialsViews.com REVIEWFunctional and synthesis diversity of graphene oxide (GO) has led to various fundamental and applied scientifi c explorations. GO can be viewed as an in-plane, hybrid 2D lattice consisting of sp2 and sp3 carbon regions. Engineering the type and distribution of sp3 regions can tune the physical properties of resultant GO. This article reviews the development in the fi eld of GO since the 19th century, with a thorough discussion on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 130 publications
(207 reference statements)
2
29
0
Order By: Relevance
“…We observed similar results using bottle test experiments and zeta potential measurements (Figure and Table ). As observed by many, GO dispersion in solvents such as water and EG which have a dipole moment >1.8 for polar solvents shows good dispersion stability . It was also observed that for nonpolar solvents, the dipole moment >3.8 exhibited better dispersion stability .…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…We observed similar results using bottle test experiments and zeta potential measurements (Figure and Table ). As observed by many, GO dispersion in solvents such as water and EG which have a dipole moment >1.8 for polar solvents shows good dispersion stability . It was also observed that for nonpolar solvents, the dipole moment >3.8 exhibited better dispersion stability .…”
Section: Resultsmentioning
confidence: 57%
“…These oxygen‐containing functional groups allow GO to be hydrophilic, and this attribute yields stable dispersions in water and other polar solvents, such as N ‐methylpyrrolidinone (NMP), dimethyl formamide (DMF), and tetrahydrofuran (THF), among others . Due to the highly functionalized surface, sp 2 / sp 3 bonds, and exceptional stability in solvents, GO can be easily manipulated and used as a precursor for numerous graphene‐based materials …”
Section: Introductionmentioning
confidence: 99%
“…The presence of oxygen functionalities causes a decrease of GO conductivity but, on the other hand, it improves GO solubility in aqueous solutions and allows the interaction with a number of chemical entities. Moreover, water solubility is consistent with the higher biological compatibility of GO compared to graphene that needs to be properly supported in order to be able to interact with biological substrates [19,20]. These peculiar characteristics have been considered promising for the development of a variety of biosensing strategies in which graphene material has been applied as a transducer of biological signals in electrochemical, fluorescence and impedance biosensors [21][22][23][24].…”
Section: Introductionmentioning
confidence: 80%
“…Graphene oxide has attracted the interest of researchers due to its heterogeneous chemical and electronic structure (Dreyer et al 2010). The unique mechanical and electrical characteristics of graphene oxide have been widely investigated and utilized in optical materials, plastic electronics, biomolecular labels, drug delivery, and biosensors (Zhu et al 2010;Pan, Sahoo, and Li 2012;Galande et al 2014). Significantly, graphene oxide has excellent solubility in water and various other solvents, benefiting from ionic groups on the periphery of the carbon sheets (Dreyer et al 2010).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%